Mesh-based Dynamic Location Service In WSANs by a Team of Robots - Zhou, Yuanye (Université d'Ottawa / University of Ottawa, 2015)
A team of robots (also called actors) in Wireless Sensor and Actor Networks (WSANs) may not be able to optimally cover an area. Hence, after an event is reported by a sensor, all robots may not be quickly reachable for possible action in time. Furthermore, sensors may not be able to immediately deliver a report to a nearby robot. In this research work, we focus on a dynamic location service to deal with a sequence of multiple events in WSANs. We propose a novel dynamic mesh-based protocol (DMesh) to boost real-time performance of the location service. We investigate new strategies for efficient event coverage, so that the robot team may appropriately partition, visit sensors periodically, and minimize the reporting delay while preserving the ability to respond, possibly with increasing number of robots as an event (such as a re) progresses and more robots arrive near the scene.